Chromosome‐scale assembly and whole‐genome sequencing of 266 giant panda roundworms provide insights into their evolution, adaptation and potential drug targets. (28th October 2021) - Han, Lei; Lan, Tianming; Li, Desheng; Li, Haimeng; Deng, Linhua; Peng, Zhiwei; He, Shaowen; Zhou, Yanqiang; Han, Ruobing; Li, Lingling; Lu, Yaxian; Lu, Haorong; et al.
Abstract: Helminth diseases have long been a threat to the health of humans and animals. Roundworms are important organisms for studying parasitic mechanisms, disease transmission and prevention. The study of parasites in the giant panda is of importance for understanding how roundworms adapt to the host. Here, we report a high‐quality chromosome‐scale genome of Baylisascaris schroederi with a genome size of 253.60 Mb and 19, 262 predicted protein‐coding genes. We found that gene families related to epidermal chitin synthesis and environmental information processes in the roundworm genome have expanded significantly. Furthermore, we demonstrated unique genes involved in essential amino acid metabolism in the B. schroederi genome, inferred to be essential for the adaptation to the giant panda‐specific diet. In addition, under different deworming pressures, we found that four resistance‐related genes ( glc ‐ 1, nrf ‐ 6, bre ‐ 4 and ced ‐ 7 ) were under strong positive selection in a captive population. Finally, 23 known drug targets and 47 potential drug target proteins were identified. The genome provides a unique reference for inferring the early evolution of roundworms and their adaptation to the host. Population genetic analysis and drug sensitivity prediction provide insights revealing the impact of deworming history on population genetic structure of importance for disease prevention.